New scheme of intermittent benznidazole administration in patients chronically infected with Trypanosoma cruzi: Clinical, parasitological, and serological assessment after three years of follow-up - Alvarez, María Gabriela (2020)
In a pilot study, we showed that the intermittent administration of benznidazole in chronic Chagas disease patients resulted in a low rate of treatment suspension and therapeutic failure, as assessed by quantitative PCR (qPCR) at the end of treatment. Here, a 3-year posttreatment follow-up study of the same cohort of patients is presented. The treatment scheme consisted of 12 doses of benznidazole at 5 mg/kg of body weight/day in two daily doses every 5 days. Parasite load, Trypanosoma cruzi-specific antibodies, and serum chemokine levels were measured prior to treatment and after a median follow-up of 36 months posttreatment by DNA minicircle kinetoplastid and nuclear DNA satellite sequence qPCR methods, conventional serological techniques, a Luminex-based assay with recombinant T. cruzi proteins, and a cytometric bead array. At the end of follow-up, 14 of 17 (82%) patients had negative qPCR findings, whereas three of 17 (18%) had detectable nonquantifiable findings by at least one of the qPCR techniques. A decline in parasite-specific antibodies at 12 months posttreatment was confirmed by conventional serological tests and the Luminex assays. Monocyte chemoattractant protein 1 levels increased after treatment, whereas monokine induced by gamma interferon levels decreased. New posttreatment electrocardiographic abnormalities were observed in only one patient who had cardiomyopathy prior to treatment. Together, these data strengthen our previous findings by showing that the intermittent administration of benznidazole results in a low rate of treatment suspension, with treatment efficacy comparable to that of a daily dose of 5 mg/kg for 60 days.